Examining Learners’ Experiences and Challenges with Peer Assessment in Bhutanese Classrooms: An Explorative Study - Thinley Wangmo; Pema Youden (Journal of English Language Teaching and Linguistics, 2025)
This exploratory study investigates the experiences and challenges of Bhutanese students with peer assessment in an Academic Skills module. The research focuses on learners' familiarity, attitudes, and perceptions of fairness regarding peer assessment and examines the correlation between grades assigned by peers and teachers. Using a mixed-methods approach, the study collects both qualitative and quantitative data through surveys, observations, and ANOVA analysis. Findings indicate a generally positive reception of peer assessment, with most students perceiving it as beneficial to their learning and assignments. However, some concerns about fairness, reliability, and potential biases were noted, underscoring the need for clear guidelines and training. The ANOVA results show no statistically significant difference between peer and tutor assessment scores, suggesting that peer assessments can be as reliable as teacher assessments. This research provides valuable insights for educators and policymakers in Bhutan to enhance student engagement and learning outcomes through well-structured peer assessment practices, contributing to the broader discourse on effective assessment methods in diverse educational settings.